Time-dependent stress–strain behaviour due to viscous properties of geogrid reinforcement. Issue 6 (December 2003) - Hirakawa, D.; Kongkitkul, W.; Tatsuoka, F.; Uchimura, T.
Abstract : A series of conventional and unconventional tensile tests were performed on six types of geosynthetic reinforcement to evaluate their viscous properties. It is shown that the isochronous model, according to which the load (or the stress) is a unique function of instantaneous strain and elapsed time, is unable to explain the major viscous aspects of the test results. In particular the model is unable to predict the stress–strain behaviour and rupture strength observed after loading is restarted at a constant strain rate following a creep loading or stress relaxation stage. It is argued that the widely prevailing concept that creep is a degrading phenomenon requiring the design strength to be reduced with an increase in the design lifetime is not realistic under typical field conditions where the stress–strain property does not deteriorate noticeably with time. It is also argued that this concept stems from the isochronous model. A non-linear three-component model is proposed to simulate the viscous aspects of the strength and deformation characteristics of the tested geosynthetic reinforcements. It is shown that this rheology model can simulate very well the experimental results obtained by the present study.